Resveratrol Inhibits Glycine Receptor-Mediated Ion Currents - Lee, Byung-Hwan; Hwang, Sung-Hee; Choi, Sun-Hye; Kim, Hyeon-Joong; Jung, Seok-Won; Kim, Hyun-Sook; Lee, Joon-Hee; Kim, Hyung-Chun; Rhim, Hyewhon; Nah, Seung-Yeol (PHARMACEUTICAL SOC JAPAN, 2014)
Resveratrol is found in grapes, red wine, and berries. Resveratrol has been known to have many beneficial health effects, such as anti-cancer, neuroprotective, anti-nociceptive, and life-prolonging effects. However, the single cellular mechanisms by which resveratrol acts are relatively unknown, especially in terms of possible regulation of receptors involved in synaptic transmission. The glycine receptor is an inhibitory ligand-gated ion channel involved in fast synaptic transmission in spinal cord. In the present study, we investigated the effect of resveratrol on human glycine receptor channel activity. Glycine alpha 1 receptors were expressed in Xenopus oocytes and glycine receptor channel activity was measured using a two-electrode voltage clamp technique. Treatment with resveratrol alone had no effect on oocytes injected with H2O or on oocytes injected with glycine alpha 1 receptor cRNA. In the oocytes injected with glycine alpha 1 receptor cRNA, co- or pre-treatment of resveratrol with glycine inhibited the glycine-induced inward peak current (I-GIy) in a reversible manner. The inhibitory effect of resveratrol on I-GIy was also concentration dependent, voltage independent, and non-competitive. These results indicate that resveratrol regulates glycine receptor channel activity and that resveratrol-mediated regulation of glycine receptor channel activity is one of several cellular action mechanisms of resveratrol for pain regulation.
Keywords: ACETYLCHOLINE-RECEPTOR; PROTECTS; CHANNELS; SITES; BRAIN